SK2 Channels Associate With mGlu1α Receptors and CaV2.1 Channels in Purkinje Cells - Luján, Rafael; Aguado, Carolina; Ciruela, Francisco; Arus, Xavier Morató; Martín-Belmonte, Alejandro; Alfaro-Ruiz, Rocío; Martínez-Gómez, Jesús; de la Ossa, Luis; Watanabe, Masahiko; Adelman, John P.; Shigemoto, Ryuichi; Fukazawa, Yugo (Frontiers in Cellular Neuroscience, 2018)
The SK2 subtype of small-conductance, Ca2+-activated K+ (SK) channels regulate the spike firing frequency and the modulation of Ca2+ transients in Purkinje cells. To understand the molecular basis by which SK2 channels mediate these functions, we analysed the exact location and densities of SK2 channels along the neuronal surface of the mouse cerebellar Purkinje cells using highly sensitive SDS-digested freeze-fracture replica labelling (SDS-FRL) combined with quantitative analyses. Immunogold particles for SK2 were observed on post- and pre-synaptic compartments showing both scattered and clustered distribution patterns. We found an axo-somato-dendritic gradient of the SK2 particle density increasing twelve-fold from soma to dendritic spines. Using two different immunogold approaches, we also found that SK2 immunoparticles were frequently adjacent to, but never overlap with, the postsynaptic density of excitatory synapses in PC spines. Co-immunoprecipitation analysis demonstrated that SK2 channels form macromolecular complexes with two types of proteins that mobilize Ca2+: CaV2.1 channels and mGlu1α receptors in the cerebellum. Freeze-fracture replica double-labelling showed significant co-clustering of particles for SK2 with those for CaV2.1 channels and mGlu1α receptors. SK2 channels were also detected at presynaptic sites, mostly at the presynaptic active zone, where they are close to CaV2.1 channels, though they are not significantly co-clustered. These data demonstrate that SK2 channels located in different neuronal compartments can associate with distinct proteins mobilizing Ca2+, and suggest that the ultrastructural association of SK2 with CaV2.1 and mGlu1α provides the mechanism that ensures voltage (excitability) regulation by distinct intracellular Ca2+ transients in Purkinje cells.